Study of sporotrichosis at the national and international level with a statistical focus: a systematic review of zoonosis (Research, Society and Development, 2020)
The studies of sporotrichosis, a zoonosis that has aroused concern in public health and a lack of reports and technical reports, deserve special attention, since it is a zoonosis with few reports on the part of the public sector as an incentive to health actions and for this reason. For this reason, it is important to develop studies that point to epidemiological outbreaks in urban and rural areas. Sporotrichosis is a chronic subacute infection that affects humans and pets, especially felines. This infection generally affects subcutaneous tissues and skin and due to factors other than immune resistance, it can reach internal organs and lead to death. The objective lay in a descriptive statistical analysis and in the verification of the main findings and interpretations about “sporotrichosis” in a scientific environment whose publications occurred in Brazil and abroad. As a methodology, the statistical software RStudio (RStudio Team, 2015) and IBM SPSS Statistics 20 (SPSS, 2011) were used for statistical analysis of hospitalizations in Brazil between 1992 to 2015, with sequential Mann-Kendall and Pettit tests. And, studies on “sporotrichosis” in a scientific environment whose publications will take place in Brazil and abroad in the years 2009 to 2019, on the Scielo platform of the years 2018 and 2019, a systematic literature review was carried out. It was found that recent research has addressed the clinical diagnosis and ways of developing sporotrichosis with their respective treatments, with the South and Southeast regions with greater evidence of the disease and an increase in hospitalizations since 2008.